2008
DOI: 10.1128/cvi.00418-07
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Recombinant Adenovirus Type 5, Vaccinia Virus, Modified Vaccinia Ankara Virus, and DNA Antigen Expression In Vivo and the Induction of Memory T-Lymphocyte Responses

Abstract: While a new generation of vaccine vectors has been developed for eliciting cellular immune responses, little is known about the optimal routes for their administration or about the ramifications of the kinetics of in vivo vaccine antigen expression for immunogenicity. We evaluated the kinetics of vaccine antigen expression by real-time in vivo photon imaging and showed dramatic differences in these kinetics using different vectors and different routes of administration. Further, using a gamma interferon enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 26 publications
0
46
0
Order By: Relevance
“…4 and 7). These data may also indicate why when poxvirus vectors are used levels of T cell response are generally lower than in vaccination strategies that utilize replicationdeficient adenovirus vectors (9,27,61,62,77). At this moment, it is not known how MVA-infected ALDC affect surface receptor expression of bystander cells, but our preliminary data indicate that one or more soluble factors are involved in this phenomenon.…”
Section: Discussionmentioning
confidence: 70%
“…4 and 7). These data may also indicate why when poxvirus vectors are used levels of T cell response are generally lower than in vaccination strategies that utilize replicationdeficient adenovirus vectors (9,27,61,62,77). At this moment, it is not known how MVA-infected ALDC affect surface receptor expression of bystander cells, but our preliminary data indicate that one or more soluble factors are involved in this phenomenon.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies from our laboratory have shown that rAd expressing a luciferase transgene (rAd-Luc) generates highlevel transgene expression for approximately 1 week in wildtype mice (20). In these studies, differences between the clearance of transgene expression in wild-type and athymic mice after rAd-Luc administration suggested that the kinetics of this clearance might be associated with the generation of cellular immune responses.…”
mentioning
confidence: 67%
“…In these studies, differences between the clearance of transgene expression in wild-type and athymic mice after rAd-Luc administration suggested that the kinetics of this clearance might be associated with the generation of cellular immune responses. In fact, a relationship between the rate of clearance of transgene expression and the generation of longterm memory cellular immune responses was noted (20). Since vaccine antigen (Ag) clearance can limit the magnitudes of adaptive immune responses, and these responses are associated with the magnitudes of the elicited memory cellular responses, we are evaluating changing the kinetics of rAddelivered antigen clearance as a strategy for enhancing rAd vaccine-elicited memory responses.…”
mentioning
confidence: 99%
“…Innate Immune Cells-We have previously shown that antigen expression during the first 3 days following plasmid DNA inoculation influenced the strength of the vaccine-induced memory T cell immune response (1). Because DNA vaccination is associated with the accumulation of both NK and NKT cells at the site of inoculation (2), we sought to determine whether these cell populations modulate plasmid DNA-elicited adaptive immune responses.…”
Section: Dna Vaccine Antigen Expression Damping Is Dependent Onmentioning
confidence: 99%
“…Plasmid DNA vaccine-induced T cell memory responses are potentiated by innate immune responses that are generated during the first days after vaccination (1). At that time Natural Killer (NK) 2 and Natural Killer T (NKT) cells are attracted to the site of vaccine administration (2).…”
mentioning
confidence: 99%